Pengaruh Pola Asuh Orang Tua dalam Menstimulasi Kecerdasan Verbal Linguistik pada Anak Usia Dini - Putri Oktaviani, Anisa; Yuntina, Lily; Intan Anggraeni, Rita (Neolectura, 2025)
This study aims to determine the influence of parenting patterns and how much influence it has on verbal linguistic intelligence in early childhood at KB Islam Al-Firdaus. The method used is quantitative with an associative approach. Data collection techniques were carried out through questionnaires with a total of 35 parents of students as respondents, all items were declared valid and reliable with Cronbach's Alpha greater than 0.6. The results of the analysis showed a coefficient of determination (R²) of 0.742, which means that parenting patterns contribute 74.2% to verbal linguistic intelligence, the remaining 25.8% is influenced by other factors not included in this study. The t-test produced t-count = 9.737 with a significance of 0.000